Language Policy and Planning (Study of Indonesian and Republic of Korea Language Literacy) - Ryeo, Park Jin; Wicaksono, Andri; Herlisya, Destia (IJLHE: International Journal of Language, Humanities, and Education, 2018)
This study discusses theoretically - practically on language policy, language politics, language planning in Indonesia, and interculturation of Indonesian and Korean culture. The method used is a literature study by including a study of policies and politics of similar languages. The results of the study show several things regarding language policy, the official language of the state, language planning, language politics, and language defense in the world, in Indonesia since pre-independence until now, in the Republic of Korea, Indo-Korean interculturation in language.